Genipin inhibits the invasion and migration of colon cancer cells by the suppression of HIF-1α accumulation and VEGF expression. (June 2018) - Lee, Suk-young; Kim, Hong Jun; Oh, Sang Cheul; Lee, Dae-Hee
Abstract: Hypoxia-inducible factor-1 (HIF-1) and vascular endothelial growth factor (VEGF) play important roles in cancer progression in various cancer cell lines. Although genipin, a constituent of Gardenia fruit, has been shown to have anti-tumor activity, its role in the suppression of HIF-1 and its downstream target genes is not well understood. We examined the effect of genipin on the intracellular level of HIF-1α and extracellular level of VEGF using the colon cancer cell line HCT116. We observed that genipin suppressed the accumulation of HIF-1α under hypoxia in various cancer cell lines, including HCT116, via the modulation of protein degradation. Genipin also suppressed the expression of VEGF and the invasion of colon cancer cells by blocking the extracellular signal-regulated kinase signaling pathway. Taken together, our results provide new insights into the potential role of genipin in suppressing colon cancer progression. Highlights: Genipin inhibits accumulation of HIF-1α and VEGF expression in human colon cancer. Genipin exerts anti-invasion effect on human colon cancer cells. Genipin-induced anti-cancer effect is exerted by Akt and ERK signaling pathways.